Amos: A historical-geographical view - Burger, J. A. (Journal for semitics, 1992)
Different methods are used to span the gap between texts and their historical settings. It is the intention of this article to underline the importance of an indispensable tool in this respect, namely historical geography. This perspective will be applied, by considering the historical-geographical role of the border region of Tekoa, in the life of the prophet Amos. In this day and age of interdisciplinary contact, much more use should be made of historical-geographical information on Palestine and the other lands of the Bible. Theologians should avail themselves of this information relevant to the biblical texts, as this vast knowledge of the historical geographer lies waiting to be utilized.